Entrepreneurship and COVID-19: Opportunities in the pandemic (Research, Society and Development, 2021)
This paper aims to investigate the opening of new businesses during this COVID-19 pandemic period in Brazil. A qualitative study, of a descriptive nature, with an investigative method based on basic qualitative research. The data collection was done through a focus group, applying a semi-structured interview to a group of nine participants, and the data were submitted to the Analysis of Nucleus of Sense, with the aid of the software IRAMUTEQ. The results showed that entrepreneurs saw new opportunities through digital social networks (Instagram, Facebook and WhatsApp), motivated by curiosity and the opportunity provided by the COVID-19 pandemic. The research evidence contributes to an entrepreneurial awakening, which seeks to seize opportunities and reach the challenging market. Once aware of the opportunities and the pent-up demand of the consuming public through social networks, new Marketing strategies can be adopted to leverage the new ventures and meet the expectations of consumers limited by the mobility restrictions and social relations imposed during the pandemic.